Morphometric changes in Watznaueria barnesiae across the mid Cretaceous: Paleoecological implications - Bettoni, Chiara; Erba, Elisabetta; Castiglione, Silvia; Raia, Pasquale; Bottini, Cinzia (2024)
This study reveals moderate yet important variations in Watznaueria barnesiae coccolith and central unit size throughout the Aptian–late Cenomanian (27 my) time interval in western Tethys. A new statistical approach was applied to determine whether non-random size trends apply to these metrics and to identify possible links between their variation and fertility or temperature. During OAE 1a, W. barnesiae coccoliths were the smallest and the most elliptical, with reduced central unit size. A further minor size decrease occurs during OAE 1b but not during OAE 1d. From the middle Albian to the middle Cenomanian, larger and less elliptical coccoliths are observed, with unchanged central unit dimensions. These results, together with concomitantly larger size changes in Biscutum constans confirm that W. barnesiae is a tolerant taxon. High-frequency, high-amplitude paleoenvironmental changes during the Aptian–early Albian indicate that temperature and fertility – either individually or in combination – had no direct impact on the mean coccolith size and potentially other factors affected coccolith size. Instead, lower nutrients with lower temperatures probably played a role in promoting larger W. barnesiae but smaller B. constans coccoliths during the middle Albian–Cenomanian. The size and ellipticity changes during OAE 1a and 1b were the strongest, likely resulting from ocean acidification and trace metal inputs, in addition to (or independently of) fertility and temperature variations.